2010
DOI: 10.1007/s00429-010-0292-7
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of Mauthner cells in the brain of Labeo rohita as revealed by NADPH-d and nNOS immunohistochemistry

Abstract: Nitric oxide (NO) is well demonstrated to act as a neuronal messenger in neurotransmission in vertebrate animals. We are for the first time reporting nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) and neuronal nitric oxide synthase (nNOS) in the Mauthner cells (MC) of the carp, Labeo rohita brain during post-embryonic development. The NADPH-d and nNOS-positive MC were seen intensely labeled in all young stages on either side of the ventricle in the hindbrain. In adult, these cells were modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(50 reference statements)
1
3
0
Order By: Relevance
“…A pair of Mauthner cells (MC) was seen in the hindbrain labeled with nNOS at the level of eighth cranial nerve. nNOS-ir MC were observed in all the developing stages except the adult brain (already reported in Palande et al, 2011). Caudally in the hindbrain, the motor nucleus of vagal nerve (nXm) was intensely stained with nNOS in all the developing stages ( Fig.…”
Section: Rhombencephalonsupporting
confidence: 54%
See 1 more Smart Citation
“…A pair of Mauthner cells (MC) was seen in the hindbrain labeled with nNOS at the level of eighth cranial nerve. nNOS-ir MC were observed in all the developing stages except the adult brain (already reported in Palande et al, 2011). Caudally in the hindbrain, the motor nucleus of vagal nerve (nXm) was intensely stained with nNOS in all the developing stages ( Fig.…”
Section: Rhombencephalonsupporting
confidence: 54%
“…Demonstration of nNOS in the NR during development may suggest a role of NO in gestation, startle responses and possibly a role in the regenerating cells of the damaged spinal cord. In our earlier study, we have already demonstrated the presence of nNOS in Mauthner cells (MC) during ontogeny, suggesting a role of NO in startle response of L. rohita (Palande et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…This last feature ranges from their living virtually alone to living in groups of considerable numbers of individuals of the same species, and from spending their entire lives swimming continuously to living on the surface bed almost permanently (which places their maintenance of homeostasis under enormous water pressure conditions) and to being able to spend short or long periods out of the water, some flying through the air and others crawling on land. Furthermore, mainly owing to the actions of M-cell (Mauthner Cell) neurons, detected in areas of their brain (hindbrain), fish are provided with the unique possibility of an extremely quick escape response (called C-start) towards the direction of immediate avoidance from a predator or in cases of hunting near the water surface that they must leave as soon as possible (Eaton et al 1991;Fetcho 1991;Canfield & Rose 1993;Svoboda & Fetcho 1996;Zottoli & Freemer 2003;Tsunehiko & Yoichi 2008;Koyama et al 2011;Palande et al 2011). Finally, fish express 'happiness', 'bad moods', aggressiveness and stress mainly by specific movements, body surface coloration changes (usually by changing to a dark colour) (Falcon et al 2010) and by refusing food.…”
Section: Fish Brain-nervous System Capacitiesmentioning
confidence: 99%
“…1991; Fetcho 1991; Canfield & Rose 1993; Svoboda & Fetcho 1996; Zottoli & Freemer 2003; Tsunehiko & Yoichi 2008; Koyama et al. 2011; Palande et al. 2011).…”
Section: Fish Brain–nervous System Capacitiesmentioning
confidence: 99%